Borane-catalyzed cascade Friedel–Crafts alkylation/[1, 5]-hydride transfer/Mannich cyclization to afford tetrahydroquinolines. Issue 3 (4th January 2022) - Zhang, Bei-Bei; Peng, Shuo; Wang, Feiyi; Lu, Cuifen; Nie, Junqi; Chen, Zuxing; Yang, Guichun; Ma, Chao
Abstract : We report a redox-neutral annulation reaction of tertiary amines with electron-deficient alkynes under metal-free and oxidant-free conditions. Abstract : An unprecedented redox-neutral annulation reaction of tertiary anilines with electron-deficient alkynes was developed that proceeds through a cascade Friedel–Crafts alkylation/[1, 5]-hydride transfer/Mannich cyclization sequence. Under B(C6 F5 )3 catalysis, a range of functionalized 1, 2, 3, 4-tetrahydroquinolines were facilely constructed in moderate to good yields with exclusive 3, 4- anti -stereochemistry. The commercial availability of the catalyst and the high atom and step economy of the procedure, together with metal-free and external oxidant-free conditions, make this an attractive method in organic synthesis.